Pengaruh Return On Asset, Equity, Dan Size Bank Terhadap Risiko Likuiditas Pada Bpr Syariah Di Indonesia - Handayania, Suci; Rahmizal, Maizul; Aswan, Khairil (Indonesian Journal of Applied Accounting and Finance, 2022)
This study aims to analyze the effect of return on assets (ROA), equity, and bank size on liquidity risk at Islamic BPRs in Indonesia. The sample in this study was 40 banks registered with the Financial Services Authority where the sampling used purposive sampling and the analysis method used was panel data regression. The data were tested using Eviews 12 software. The results showed that ROA has a negative and significant effect on liquidity risk, equity has a negative and significant effect on liquidity risk, and bank size has a positive and insignificant effect on liquidity risk.